2007
DOI: 10.1377/hlthaff.26.2.520
|View full text |Cite
|
Sign up to set email alerts
|

How Stable Is Medicaid Coverage For Children?

Abstract: We examined Medicaid coverage patterns in five states for children who were covered as of December 2003. Looking back three years, we found that Medicaid was a source of continuous coverage for sizable proportions of children (43-66 percent were covered for two or more years) but a revolving door for others (16-41 percent had gaps). In all states, gaps were short, from two to four months. Continuity implies that states can demand more of the health care system to improve the quality of care; short gaps imply t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…[12][13][14]16 Other analyses have used vital statistics and Medicaid data to study utilization and coverage patterns. 6,17 Secondary analyses of administrative data are often several steps removed from the real-life experiences of vulnerable families, and studies conducted in physicians' offi ces miss the invisible families who are unable to visit health care facilities. To our knowledge, limited information has been collected directly from families living in poverty about factors affecting access to medical care and how insurance status affects their situations.…”
Section: Insur a Nc E Acc Es S A Nd He A Lt H C A R Ementioning
confidence: 99%
“…[12][13][14]16 Other analyses have used vital statistics and Medicaid data to study utilization and coverage patterns. 6,17 Secondary analyses of administrative data are often several steps removed from the real-life experiences of vulnerable families, and studies conducted in physicians' offi ces miss the invisible families who are unable to visit health care facilities. To our knowledge, limited information has been collected directly from families living in poverty about factors affecting access to medical care and how insurance status affects their situations.…”
Section: Insur a Nc E Acc Es S A Nd He A Lt H C A R Ementioning
confidence: 99%
“…20 It may also be attributable to the fact that this state had not yet implemented simplifications in Medicaid-CHIP enrollment or renewal, which have been shown to reduce instances of uninsurance for children from low-income families. [46][47][48] However, because Massachusetts had high Medicaid-CHIP eligibility levels and rates of insurance prereform, the remaining uninsured CSHCN might be hard-to-reach subjects or undocumented. 49,50 Because the ACA specifically includes children in the individual mandate and incentivizes states to simplify Medicaid-CHIP enrollment and renewal, reductions in uninsurance may be greater under the ACA than under Massachusetts health reform.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A majority of these uninsured children qualify for publicly-funded insurance programs, such as Medicaid and the State Children's Health Insurance Programs (SCHIP), but have either lost coverage or become disenrolled due to various barriers. [13][14][15][16] Oregon has a high rate of uninsured children, 13,17 and over 60% of uninsured Oregon children appeared to be eligible for some form of public coverage in 2004-a higher percentage than is estimated for uninsured children nationally. 11,18 As struggles to reauthorize SCHIP continue, [19][20][21][22] Oregon and several other states are focused on enrolling uninsured but eligible low-income children.…”
mentioning
confidence: 99%
“…Past research has concluded that most low-income parents are familiar with Medicaid and SCHIP, but restrictive regulations and confusing organizational structures keep public health insurance out of reach for some low-income families and contribute to coverage instabilities for others. 14,17,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Less is known about how parents feel about public insurance offerings and whether they believe that getting and maintaining coverage is worth the effort required. Despite the wealth of evidence linking insurance to better health care outcomes, how much does health insurance matter to poor families?…”
mentioning
confidence: 99%
See 1 more Smart Citation